2018
DOI: 10.1021/acs.est.8b02771
|View full text |Cite
|
Sign up to set email alerts
|

Cost Optimization of Osmotically Assisted Reverse Osmosis

Abstract: We develop a nonlinear optimization model to identify minimum cost designs for osmotically assisted reverse osmosis (OARO), a multi-staged membrane-based process for desalinating high salinity brines. The optimization model enables comprehensive evaluation of a complex process configuration and operational decision space that includes nonlinear process performance and implicit relationships between membrane stages, saline sweep cycles, and make-up, purge, and recycle streams. The objective function minimizes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 41 publications
1
60
0
Order By: Relevance
“…They optimized operating and design variables and found that the hybrid system has a higher overall recovery and lower operating cost than the MSF system and better product water quality than RO alone. Bartholomew [157] developed a cost optimization model for osmotically assisted RO, in which they investigated the relationship between membrane stages, saline sweep cycles, and makeup, purge and recycle streams for high-salinity feeds in the range of 50,000 to 125,000 ppm TDS. The optimized design resulted in costs less than $6/m 3 water with water recoveries between 30-70%.…”
Section: Modelling Of Hybrid Desalination Technologiesmentioning
confidence: 99%
See 3 more Smart Citations
“…They optimized operating and design variables and found that the hybrid system has a higher overall recovery and lower operating cost than the MSF system and better product water quality than RO alone. Bartholomew [157] developed a cost optimization model for osmotically assisted RO, in which they investigated the relationship between membrane stages, saline sweep cycles, and makeup, purge and recycle streams for high-salinity feeds in the range of 50,000 to 125,000 ppm TDS. The optimized design resulted in costs less than $6/m 3 water with water recoveries between 30-70%.…”
Section: Modelling Of Hybrid Desalination Technologiesmentioning
confidence: 99%
“…The optimized design resulted in costs less than $6/m 3 water with water recoveries between 30-70%. They studied 3 cases: (1) feed TDS of 75 g/L and 50% water recovery, (2) feed TDS of 75 g/L and 70% water recovery, and (3) feed TDS of 125 g/L and 40% water recovery [157]. They found that cost-optimal unit water cost was the lowest for case 1, as shown in Figure 38A.…”
Section: Modelling Of Hybrid Desalination Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanical vapor compression (MVC) brine concentrators are currently the state-of-theart technology for concentrating hypersaline brine, typically up to ≈250 g/L total dissolved solids (TDS), which can then be passed to crystallizers for zero-liquid-discharge [9,10]. While MVC possesses a high recovery of latent heat and can achieve a specific energy consumption in the range of 20-40 kWh e /m 3 of feedwater [9][10][11], the technology remains energy-intensive, primarily uses electrical energy for vapor compression, and requires stainless steel and titanium materials for avoiding corrosion, resulting in high capital cost. Furthermore, based on estimates of second-law efficiencies for zero-liquid-discharge, MVC brine concentrators were shown to be less than half as efficient (8.5% and 11.6% second-law efficiency for single-and two-stage MVC) as multi-effect evaporators used for crystallization (24.4% second-law efficiency) [12], indicating that efforts should focus more on improving the energy efficiency of the brine concentration step in zeroliquid-discharge applications.…”
Section: Introductionmentioning
confidence: 99%